Multiple mechanisms determine the effect of warming on plant litter decomposition in a dryland. (June 2020) - Chuckran, Peter F.; Reibold, Robin; Throop, Heather L.; Reed, Sasha C.
Abstract: In drylands, where soil fertility is typically low, plant litter decomposition provides particularly critical carbon and nitrogen inputs into soil. Although climate change is projected to increase the already large global extent of drylands, it is unknown how warmer temperatures will affect core ecosystem processes, such as plant litter decomposition, in these systems. To address this key unknown, we conducted a litterbag study in a long-term dryland warming experiment in southeastern Utah, USA. Unexpectedly, we did not find an overall effect of warming on leaf litter mass loss over time. Instead, our results indicated both positive and negative effects of warming on mass loss which offset one another. In particular, our findings suggested that a warming-induced degradation of biological soil crusts (soil surface community of mosses, lichens, and/or cyanobacteria that live in drylands worldwide) increased soil-litter mixing, thereby accelerating decomposition. Results also suggested that a warming-induced reduction in litter moisture slowed decomposition. In addition, we found that warming lowered the carbon-to-nitrogen ratio of the decomposing litter. These results showed that warming did not alter the total litter mass-loss rates in this ecosystem, but that decomposition patterns were affected through more nuanced changes to both the biological and physical environment of dryland soils. Highlights: Use of a long-term warming experiment to study dryland litter decomposition. No overall impact of warming on mass loss because of multiple opposing controls. Warming degraded biocrust, which increased soil-litter mixing. Increased soil-litter mixing accelerated decomposition. Warming reduced rates of litter mass loss, likely due to moisture limitations.